STRATEGI PENGEMBANGAN USAHA TEH DI PT. PERKEBUNAN TAMBI WONOSOBO DENGAN PENDEKATAN BUSINESS MODEL CANVAS - Dwi Septian, Yoshua Agung; Yuliawati, (JURNAL AGRIBISAINS, 2023)
Tea is a drink that is quite popular all over the world after coffee. The large number of companies engaged in tea production makes the competition very fierce. PT. Perkebunan Tambi Wonosobo is a company that focuses on tea that produces various types of tea, namely black tea, green tea, and fragrant tea. The intense competition in the tea industry demands PT. Perkebunan Tambi Wonosobo to carry out business development. This study aims to identify the business model of PT. Perkebunan Tambi Wonosobo the current is evaluating and designing business model updates with the Business Model Canvas (BMC) approach. The method used is qualitative with descriptive analysis, there were 5 participants in this study from the internal party of PT. Perkebunan Tambi Wonosobo, namely Assistant Director, Head of Production Section, Head of Marketing Section, Head of Finance, and Head of HR & General Affairs Section who are purposively elected. Data were obtained through interviews using interview and observation guides. The data obtained will be carried out triangulation tests, namely source triangulation and engineering triangulation. The analysis method uses BMC. The results showed: of the nine BMC elements contained in PT. Perkebunan Tambi Wonosobo is already doing well, but the company has not taken advantage of technological advances in reaching and marketing its products. The recommended business model update for PT. Perkebunan Tambi Wonosobo's in the future is use of digital marketing, sales through e-commerce, creation of digital marketing systems, product updates, promotion through social media, and customer expansion.